Relaxation stage analysis of lithium inserted graphite. (July 2020) - Kitamura, Takashi; Takai, Shigeomi; Yabutsuka, Takeshi; Yao, Takeshi
Abstract: Relaxation analysis has been carried out on lithium graphite intercalation compound (Li-GIC) focusing on the variation of stage structure and graphene interlayer distances. X-ray diffraction coupled with the one-dimensional Rietveld analysis revealed that, after the termination of electrochemical lithium insertion, excessively formed stage I partly transforms into stage II during the relaxation process. In addition, the periodic stacking of defective lithium layers forming stage II orders the lithium occupation at the relaxation, which is more apparently observed for faster charged sample. Even after the lithium extraction, gradual stage changes from I to II accompanied by the ordering of lithium occupation in stage II have been observed at the relaxation process. Lithium ion is rather uniformly intercalated or deintercalated in the graphene interlayers, while Li-GIC turned into ordered stage structure to achieve the stable state at the relaxation time. Highlights: After Li insertion into graphite, stage I partly changes into I and II at relaxation. Lithium occupied interlayers in stage II orders at relaxation. Even for Li extraction, stage change from I to II was detected at the relaxation.